The effect of social media usage and the quality of information from the instagram account @DITJENPAJAKRI on the fulfillment of tax information needs of PKN STAN students - Al Aqilah, Muhamad Refkhi; Maharani, Arya Putri; Nagara, Devitama Patria; Gumilang, Gabiela; Sutanto, Meithasya Putri; Setiawan, Prayoga; Utomo, Rachmad (WIM Solusi Prima, 2024)
This study aims to analyze the influence of Instagram social media usage and the information quality of the @ditjenpajakri account on fulfilling the tax information needs of PKN STAN students. Using a quantitative method with a survey approach, data were collected from 97 active PKN STAN students through a questionnaire. The analysis results indicate that social media usage and the information quality of @ditjenpajakri significantly influence the fulfillment of PKN STAN students' tax information needs, with an F-test value of 0.0000. The four social media indicators—context, communication, collaboration, and connection—were well-rated by respondents, who agreed that these factors effectively meet their information needs. Most respondents agree that the content uploaded by @ditjenpajakri meets the criteria for high-quality information, including accuracy, timeliness, relevance, and completeness. It is expected that the Directorate General of Taxes will maintain and improve the quality of content on Instagram, particularly in terms of accuracy, timeliness, and relevance of information.